Generation X Consumption Behavior Model in Using Digital Transactions - Sirait, Afni; Purnama, Ida Ayu (RSF Conference Series: Business, Management and Social Sciences, 2021)
Technology is a necessity that cannot be separated from life today. Daily activities are made easier and even dismiss distance, space, and time. This convenience provides cost savings, increases time use quality, and even changes a business process. This study aims to analyze the model of consumer behavior of generation X in the use of digital transactions. This research is a quantitative approach with 73 respondents who fit the qualifications. The data was collected using a questionnaire which was then tested for validity, reliability, and model fit using the WarpPLS 6.0 analysis tool. The test results explained that consumption behavior mediated cultural factors do not directly affect the generation of digital transaction X (the value path coefficient H1 equals -0007 P = 0,28). Psychological factors have a direct influence on digital transactions Generation X (H2 has a value of path coefficients 0,12 and P = 0,15), but it has indirect influence the results of the mediation of the variable consumption behavior against the decision transaction generation digital X (the value path coefficient 0.728, P<0.001, and R-Squared 0.57) with the model fit testing the VIF value of 1.236, and the GoF value of 0.411. The limitation of this study is that the population only focuses on generation X.